Contour Restoration of Over-Resected Mandibular Angle and Lower Border by Reduction Mandibuloplasty Using Three-Dimensional Planning and Computer-Aided Design and Manufacturing Custom-Made Titanium Implants. Issue 4 (June 2018) - Woo, Jae Man; Baek, Seung-Hak; Kim, Jong-Cheol; Choi, Jin-Young
Abstract : Objective: The purpose of this clinical report was to introduce a new methodology for contour restoration of the over-resected mandible by reduction mandibuloplasty using 3-dimensional (3D) planning and computer-assisted design and manufacturing (CAD-CAM) custom-made titanium implants. Patient and method: A 20-year-old male patient had undergone reduction of the zygoma and mandibular angle and lower border for esthetic reason 1 year ago at a private clinic. However, he was not satisfied with surgical outcome and wanted to restore his original facial volume and contour. To assess the volume and dimension of resected bone, 3D-computed tomography (3D-CT) data at the original stage was superimposed with postsurgical CT. For restoration of the malar prominence, porous polyethylene malar implants with extensions into the lateral malar region (Medpor) were placed and fixed with microscrews. Custom-made titanium implants were fabricated for contour restoration of the mandibular angle and lower border using CAD-CAM technology (iDDA, Daegu, South Korea). Two-piece design per each titanium implant was adopted for easy placement and avoidance of tissue damage during placement. Thin buccal extension was incorporated for placement of screw holes. Location, direction, and length of bicortical screws were planned to avoid damage of the inferior alveolar nerve. Result: With the help of 3D planning and CAD-CAM technology, rigid fixation of the custom-made titanium implants into the mandibular angle and lower border successfully restored the contour of over-resected mandible to the original state. Conclusion: When over-resection by reduction mandibuloplasty becomes an issue, this method may be an effective treatment option for contour restoration of over-resected mandibular angle and lower border.